2020
DOI: 10.1021/jacs.0c09242
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Response to Copper Binding in Superoxide Dismutase Dynamics

Abstract: Copper/zinc superoxide dismutase (SOD) is a homodimeric metalloenzyme which has been extensively studied as a benchmark for structure-function relationships in proteins, in particular because of its implication in the familial form of the neurodegenerative disease amyotrophic lateral sclerosis. Here, we investigate microcrystalline preparations of two differently metallated forms of SOD, namely the fully mature functional Cu I ,Zn state and the E,Zn-SOD state in which the Cu site is empty. By using solid-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Investigations of the fully mature functional Cu, Zn state of superoxide dismutase and its E, Zn-state in which the Cu site is empty have shown that the metal ion after uptake does not act as a rigidification element. Using 15 N R 1 , R 1ρ experiments, it has been shown that metal binding acts rather as a switch that redistributes motional processes on different time scales and induces a coupling of the dynamics of the histidine side chains to remote key backbone elements of the protein . The SAIL approach allows selectivity of isotopically labeled aromatic rings in proteins .…”
Section: Quantification Of Dynamicsmentioning
confidence: 99%
“…Investigations of the fully mature functional Cu, Zn state of superoxide dismutase and its E, Zn-state in which the Cu site is empty have shown that the metal ion after uptake does not act as a rigidification element. Using 15 N R 1 , R 1ρ experiments, it has been shown that metal binding acts rather as a switch that redistributes motional processes on different time scales and induces a coupling of the dynamics of the histidine side chains to remote key backbone elements of the protein . The SAIL approach allows selectivity of isotopically labeled aromatic rings in proteins .…”
Section: Quantification Of Dynamicsmentioning
confidence: 99%
“…We additionally present a comparison of the results obtained with chemical shifts previously obtained on deuterated MBP in solution (Evenäs et al 2001). Considering the recent findings of previously unobserved dynamics in other, supposedly rigid, crystalline proteins (Rovó et al 2019;Bonaccorsi et al 2020), we additionally anticipate the possibility of new insight on internal motions which escaped previous determinations by X-ray and solution NMR.…”
Section: Introductionmentioning
confidence: 87%
“…Conversely the investigation of motions in a window from ps to ms revealed a multimodal response, with the metal acting as a control element and redistributing dynamic processes over multiple timescales. Moreover, a coupling was observed between motions of side chains coordinating the copper in the active site and those of distant backbone elements of the protein which are pivotal for SOD stability and efficient enzymatic activity [33]. The multitimescale dynamics unveiled in these studies by solid-state NMR are particularly difficult to observe using other methods [34], and in the specific case of SOD had escaped previous determinations by solution NMR.…”
Section: Introductionmentioning
confidence: 95%